Determining the effect of laboratory testing conditions on working parameters of the ST-25 hall thruster - Petrenko, Olexandr; Pererva, Viktor; Maslov, Viktor (Eastern-European Journal of Enterprise Technologies, 2024)
The object of this study is the ST-25 Hall thruster with limited discharge power, no more than 200 W, designed by Flight Control LLC (Ukraine). The problem that was solved in the current paper was to determine the effect of residual gas pressure in vacuum chambers on the operating parameters of the Hall thruster. To solve this task, the operating parameters of the ST-25 thruster were determined, which was tested in three vacuum chambers with different sizes of residual pressure. As a result of the laboratory study into the operating parameters of the ST-25 thruster, the volt-ampere characteristics of the engine discharge at fixed values of the working gas (xenon) flow rate were obtained. The dependences of the engine thrust on the mass flow rate of the working gas at fixed values of the discharge voltage were derived. Based on the experimental data, the dependences of the specific impulse of the engine anode unit on the discharge voltage, as well as the dependence of efficiency of the engine anode unit on the discharge voltage were calculated. The studies showed that when the residual pressure in the vacuum chamber is reduced by 2–3 times, the operating parameters of the engine increase by 15–20 %. Such a reduction in residual pressure increases thrust by 25–40 %. Special feature of the results is the determination of threshold values of residual gas pressure in vacuum chambers during experimental studies, in which the operating parameters of the Hall thruster are similar to its operating parameters under space conditions. This work’s findings could be used in practice when conducting experimental studies of electric rocket engines, when it is necessary to estimate the operating parameters of Hall thrusters that will be obtained under actual space conditions